A simple technique to readout and characterize coupled MEMS resonators - Tao, G; Choubey, B (Institute of Electrical and Electronics Engineers, 2016)
Highly sensitive microelectromechanical system (MEMS) resonators have been used for extensive applications such as mass sensing. However, these arrays are prone to process variations and are difficult to characterize due to lack of connections with each resonator. Coupled array of such sensors can enhance functionality while reducing interconnections. This scheme allows a number of sensors to be read out using a single input/output channel. By perturbing the spring constant of one resonator, two sets of eigenvalues can be measured to reconstruct the system matrix of the coupled system. However, perturbation on MEMS devices can introduce non-linear or physical change. To prevent such undesired change, this paper proposes a technique to couple an electrical resonator to an array of MEMS resonators. Two sets of eigenvalues can therefore be measured by simply connecting/disconnecting the electrical resonator. Errors introduced by frequency noise, array size, coupling strength, and damping have been analyzed. The successful coupling between electrical and mechanical resonators brings huge promise for integrated MEMS devices that could be used for single input/output multi-sensor and monitoring variations in MEMS fabrication. [2015-0299]